A single bubble rising in the vicinity of a vertical wall: A numerical study based on volume of fluid method. (1st November 2022) - Yan, Hongjie; Zhang, Huimin; Liao, Yixiang; Zhang, Heyang; Zhou, Ping; Liu, Liu
Abstract: Single bubble rising in the close vicinity of a vertical wall is one of the focuses in the field of gas-liquid two-phase flow. In this work, three-dimensional direct numerical simulation based on volume of fluid (VOF) and adaptive mesh refinement method is performed to investigate the bubble rising and wake structures near a vertical wall. The bubble migration trajectory, deformation, velocity and wake structures were analyzed under various Galileo numbers and initial wall distances. Bubbles with a Galileo number of 8.8 significantly migrate away from the wall, which is driven by the repulsive force as a result of the suppression of the vortex diffusion on the bubble surface. As the Galileo number increases, the asymmetry of the shedding vortex tends to play a vital role on the repulsive force, which is exacerbated by the presence of the vertical wall. A periodic shedding of the vortex appears behind the bubble when the Galileo number reaches at 95. Meanwhile, the bubble trajectory changes from rectilinear to spiral along with a periodic oscillation. Due to the interaction between the vertical wall and the bubble wake, a transition from a rectilinear rising path to a spiral rising path is more likely to occur compared to that without a vertical wall. The presence of a vertical wall contributes to bubble-rising oscillations. A decrease of the bubble terminal velocity due to viscous effect near the vertical wall is observed for bubbles at low Galileo numbers. However, the viscous effect is less pronounced as the Galileo number increases. Highlights: A combined numerical methods of VOF and AMR was adopted to investigated the motion of the near-wall bubble. The wall can trigger bubble-rising oscillations earlier due to the imbalance of the vortex around the bubble. The terminal velocity of the bubble is reduced with the presence of the wall, which weakens as the viscosity increase. The wall effect on terminal velocity and aspect ratio is unrelated to initial distance from the wall in our study scope.